2015
DOI: 10.1007/s10459-015-9650-9
|View full text |Cite
|
Sign up to set email alerts
|

Toward diversity-responsive medical education: taking an intersectionality-based approach to a curriculum evaluation

Abstract: Recent years have seen a rise in the efforts to implement diversity topics into medical education, using either a ‘narrow’ or a ‘broad’ definition of culture. These developments urge that outcomes of such efforts are systematically evaluated by mapping the curriculum for diversity-responsive content. This study was aimed at using an intersectionality-based approach to define diversity-related learning objectives and to evaluate how biomedical and sociocultural aspects of diversity were integrated into a medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
78
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 42 publications
(70 reference statements)
5
78
0
1
Order By: Relevance
“…Previously (Morgan et.al., 2014, 2016), we suggested that it might be helpful to include a short course on the history of anatomy that incorporated an understanding of gender issues in medical training so as to raise awareness and improve students' critical skills. Brenner and Pais () suggest that “anatomical education should not only provide knowledge, but also skills and attitudes, which can be fostered by the involvement of anatomy in medical humanities.” Transformation of the culture of medicine to encourage the formation of an inclusive organizational and educational climate, and the embedding of teaching content related to sociocultural and biomedical aspects of diversity into preclinical and clinical teaching programs, is recommended by Muntinga et al (). Even when gender issues are not formally taught, they can be embedded within the anatomy course if the teachers themselves have sufficient training, understanding and motivation.…”
Section: Recommendationsmentioning
confidence: 99%
“…Previously (Morgan et.al., 2014, 2016), we suggested that it might be helpful to include a short course on the history of anatomy that incorporated an understanding of gender issues in medical training so as to raise awareness and improve students' critical skills. Brenner and Pais () suggest that “anatomical education should not only provide knowledge, but also skills and attitudes, which can be fostered by the involvement of anatomy in medical humanities.” Transformation of the culture of medicine to encourage the formation of an inclusive organizational and educational climate, and the embedding of teaching content related to sociocultural and biomedical aspects of diversity into preclinical and clinical teaching programs, is recommended by Muntinga et al (). Even when gender issues are not formally taught, they can be embedded within the anatomy course if the teachers themselves have sufficient training, understanding and motivation.…”
Section: Recommendationsmentioning
confidence: 99%
“…2 These have been shown to influence rural career preference, particularly when combined. 3,7,8 WP refers to proportional inclusion of students representing the broader community, including those from disadvantaged backgrounds, mature age students, ethnic and cultural groups and students with a disability. 6 Widening participation (WP) and widening access (WA) are two different strategies that aim to increase the diversity of medical students entering medical school, premised to increase culturally and socially appropriate health care to help overcome disparity.…”
Section: Introductionmentioning
confidence: 99%
“…6 Widening participation (WP) and widening access (WA) are two different strategies that aim to increase the diversity of medical students entering medical school, premised to increase culturally and socially appropriate health care to help overcome disparity. 3,7,8 WP refers to proportional inclusion of students representing the broader community, including those from disadvantaged backgrounds, mature age students, ethnic and cultural groups and students with a disability. 9 WA refers more specifically to selection policies and processes that overcome inequity in meeting standard entry requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the advocacy for cultural competence already for decades, and despite the influx of female and minority students, the uptake of diversity issues in all facets of medical education has been slow. Issues are for instance addressing the (under)representation of black and minority students (5), transforming learning climate and organizational cultures (6,7), and integrating diversity issues in curricula (2,(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%